Affected-topic have: An applicative account - Cowper, Elizabeth (Linguistica Atlantica, 2017)
This paper proposes a new analysis of sentences like The tree has a bird’s nest in it, and The garden has had many flowers planted in it. I argue that have in these sentences spells out a previously unnoticed applicative head, which occupies a position below T and above the head hosting viewpoint aspect, and whose specifier receives an affected-topic interpretation. This account correctly accounts for the interactions between have and the spellout of other auxiliaries in the clause, and brings the number of distinct applicative heads in English to at least three. Parallels are observed between the behaviour of these three applicative heads and Voice, raising the question of whether Voice and Applicative heads are better thought of as forming a unified class of argument introducers. The account of affected-topic have also lends support to the dynamic theory of phases, and to a postsyntactic, realizational view of morphology.